No selection on immunological markers in response to a highly virulent pathogen in an Arctic breeding bird. (26th June 2014) - Legagneux, Pierre; Berzins, Lisha L.; Forbes, Mark; Harms, Naomi Jane; Hennin, Holly L.; Bourgeon, Sophie; Gilchrist, H. G.; Bêty, Joël; Soos, Catherine; Love, Oliver P.; Foster, Jeffrey T.; Descamps, Sébastien; et al.
Abstract In natural populations, epidemics provide opportunities to look for intense natural selection on genes coding for life history and immune or other physiological traits. If the populations being considered are of management or conservation concern, then identifying the traits under selection (or 'markers') might provide insights into possible intervention strategies during epidemics. We assessed potential for selection on multiple immune and life history traits of Arctic breeding common eiders (Somateria mollissima) during annual avian cholera outbreaks (summers of 2006, 2007 & 2008). We measured prelaying body condition, immune traits, and subsequent reproductive investment (i.e., clutch size) and survival of female common eiders and whether they were infected with Pasteurella multocida, the causative agent of avian cholera. We found no clear and consistent evidence of directional selection on immune traits; however, infected birds had higher levels of haptoglobin than uninfected birds. Also, females that laid larger clutches had slightly lower immune responses during the prelaying period reflecting possible downregulation of the immune system to support higher costs of reproduction. This supports a recent study indicating that birds investing in larger clutches were more likely to die from avian cholera and points to a possible management option to maximize female survival during outbreaks.